2013
DOI: 10.1002/stem.1327
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Adult Salivary Gland Stem Cells and a Potential Therapy for Xerostomia

Abstract: The ability to speak, swallow, masticate, taste food, and maintain a healthy oral cavity is heavily reliant on the presence of saliva, the hugely important effect of which on our everyday lives is often unappreciated. Hyposalivation, frequently experienced by people receiving radiation therapy for head and neck cancers, results in a plethora of symptoms whose combined effect can drastically reduce quality of life. Although artificial lubricants and drugs stimulating residual function are available to ameliorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(161 citation statements)
references
References 79 publications
2
157
1
1
Order By: Relevance
“…It was widely believed that acinar cells of the salivary gland are replaced through stem cell differentiation, 36 but one study has demonstrated that acinar cell proliferation accounts for postnatal growth and expansion of the salivary gland, as well as for maintenance and regeneration of the adult organ. 27 Similar mechanisms have been reported for the growth and maintenance of other glands in the digestive tract including liver and pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…It was widely believed that acinar cells of the salivary gland are replaced through stem cell differentiation, 36 but one study has demonstrated that acinar cell proliferation accounts for postnatal growth and expansion of the salivary gland, as well as for maintenance and regeneration of the adult organ. 27 Similar mechanisms have been reported for the growth and maintenance of other glands in the digestive tract including liver and pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Kinase inhibitors (Roscovitine) have been found to suppress apoptosis and temporarily inhibit cell cycle progression (G2/M cell cycle) to allow for DNA repair 16 . Ligating the main excretory duct is reported to cause proliferation of ductal cells, key to which would be the number of surviving stem/progenitor cells 17 . Ascl3+ progenitor cells were identified in developing rat submandibular glands.…”
Section: Biologic and Surgicalmentioning
confidence: 99%
“…In fact, analysis in the mouse SMG yielded the conclusion that "most, if not all, proliferative activity leading to acinar cell population maintenance occurs by self-proliferation" (Denny et al 1993). Despite this convincing body of evidence, as stem cells moved to central stage, the idea that salivary glands are maintained by stem cells became accepted (Pringle et al 2013). It is thus important to clarify the role of both stem cells and differentiated cells in maintaining the salivary glands.…”
Section: The Proliferating Salivary Glandmentioning
confidence: 99%
“…The design of restorative therapies requires knowledge of how the salivary glands normally replace aging cells or repair damaged tissue. The prevailing view is that new secretory acinar and duct cells are generated from resident adult stem cells (reviewed in Pringle et al 2013). However, the relative contributions of stem cells to salivary gland cell turnover have been unclear.…”
Section: Introductionmentioning
confidence: 99%